Do Urban Community Gardens Matter? The Case of Bulawayo Metropolitan Province in Zimbabwe - Sithole, Mkhokheli; Nkala, Peter; Dube, Nqobizitha (Richtmann Publishing, 2012)
This paper discusses the role of urban agriculture with a special focus on community gardens in urban food security andpoverty alleviation in the three high density suburbs of Magwegwe North, Nketa and Nkulumane in Bulawayo metropolitan province ofZimbabwe. Urban agriculture in Zimbabwe is in two forms; one that violates local authority by-laws whereby open pieces of land arehaphazardly cultivated and the form comprising authorised cultivation of urban gardens close to residential areas or on allocated landthough, with limited renewable user rights, by the local authority to farmers. The study focuses on the different beneficiaries, cropsgrown, output and their contributions to the household diet and income. The research is largely qualitative and uses primary datacollected from 15 interviews, 5 focus group discussions and observations on beneficiaries of community gardens in Magwegwe North,Nketa and Nkulumane high density suburbs. The results indicate that community gardens have become a significant source of freshproduce but the shortage of resources inputs, and environmental health risks remain paramount obstacles to realising the full potential ofthese gardens. We conclude that community gardens do increase access and household food security, diversity of diet and contributeimmensely to poverty alleviation among urban households.